Tubal ligation: the characterization of sterilized users of a public service - Nicolau, Ana Izabel Oliveira; Moraes, Maria Leonor Costa de; Lima, Diego Jorge Maia; Aquino, Priscila de Souza; Pinheiro, Ana Karina Bezerra (Revista da Escola de Enfermagem da USP, 2011)
The purpose of this study was to trace the contraceptive history of sterilized women and identify the associations between educational, sexual and obstetric variables and the women's age when they underwent the procedure for tubal ligation (TL). This is a retrospective documentary study performed at the Lígia Barros Costa Natural Birthing Center in Fortaleza, Ceará, with 1423 records, dating from 2005 to 2008, 277 of which referred to sterilized women. Data analysis involved applying the calculation of frequencies, Pearson's chi-square test and correlation of Pearson/Spearman. Sterilized women represented a population with low education, marital union, and a history of infrequent use of other contraceptive methods other than condoms and the pill. Numbers of pregnancies and abortions/miscarriages were related with the age of TL, unlike the variables of education and the age of the first sexual intercourse. With this knowledge at hand, nurses can improve their look towards women looking forward to TL, and thus strengthen education strategies and promote greater diversity in the alternatives for contraception.